PENGARUH SENAM NIFAS TERHADAP KECEPATAN INVOLUSI UTERI IBU POST PARTUM DI DESA GEDANGAN GROGOL SUKOHARJO - Ratna Indriati; Tunjung Sri Yulianti; Ika Fitriani Mulyanto (KOSALA : Jurnal Ilmu Kesehatan, 2014)
Abstract The Background of One of a physiological changes during the puerperium is involution uteri begin immediately after birth.Involution uteri is the clinical very important, because it ' s a possibility that the process could be disrupted bleeding parturition.Involution uteri to speed up the process, one who advocated is gymnastic exercise performed after parturition the body feel better again.However, not all the mother after partus performing gymnastic parturition with regularly every day.Based on the observation of the post partum in the village of Gedangan Sukoharjo, the mother don ' t do gymnastics parturition TFU the 3rd is two cm below the umbilical’s mother. Where as she who do gymnastics parturition, the 3rd TFU 2,5 cm below the umbilical and stomach looked strong and lax. The aim of this research is to find influence of gymnastic parturition to speed the post partum involution uteri in the village of Gedangan, grogol, Sukoharjo. This is a research Methods. The respondent are the post partum in the village of Gedangan Sukoharjo by design the experimental quasy with randomized posttest only control to comparing the puerperium gymnastic exercise between groups given treatment and the puerperium not given treatment gymnastics parturition.Which have collected data and analysis by the independent t-test with p = 0.05. Research results in respondents who do gymnastics parturition obtained 60% of respondents experienced a decline with TFU range 6.1 - 8.0 cm and 40% in the range of 4.0 - 6.0. While the respondents are not done gymnastics parturition decreased TFU all respondents (100%) are in the range of 4.0 - 6.0 cm. from the independent t-test obtained p of 0,000 so p < 0.05, which means Ho is rejected and accepted Ha. The Conclusion of the research was there is influence of gymnastics parturition against the speed of the involution of uteri maternal post partum, in the village of Gedangan Grogol Sukoharjo Keywords: gymnastics parturition, involution uteri, the post partum